SISTEM PAKAR DIAGNOSIS PENYAKIT PADA TANAMAN KELAPA SAWIT MENGGUNAKAN METODE CERTAINTY FACTOR - Supriyanto, Gunawan; Jusak, Jusak; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract:One of the main causes for high rates land degradation and low productivity in farmer’s oil palm plantation is diseases which attack farmer’s plantation. In addition, lack of farmer’s knowledge about this oil palm’s diseases becomes a major problem for farmers who want to take control of the diseases. Furthermore, there is limitation of agriculture expert the area, since their location is in rural area. The tardiness of this disease control can lead to farmer’s oil palm plantation damage and even died. From this farmer’s lack of knowledge about how to diagnose the disease and limitation of agriculture expert, in this paper we develop an expert system for diagnosing diseases in oil palm plantation by utilizing the certainty factor (CF) method. This expert system will diagnose based on the symptoms that mentioned by the farmers. From every symptom will be adapted with the existing rules and combined with CF rule point from every symptom. Hereinafter, system will gives diagnose result and procedure how to control oil palm’s disease. Result from this expert system shows that the system is able to diagnose the type of oil palm’s disease with 91,7% accuracy. This result was acquired based on farmer’s diagnose answer and compared by diagnose result that be done by oil palm specialists for 12 cases. Moreover, the system also produces advices how to control the disease for farmer based on type of the diseases.